The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1460-9568.1995.tb01074.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Barium on [3H]Noradrenalin Release from the Human Neuroblastoma SH‐SY5Y

Abstract: Replacement of Ca2+ with Ba2+ in HEPES-buffered saline stimulated [3H]noradrenalin release in the human neuroblastoma clone SH-SY5Y by up to 20% of the cell content in the absence of other secretory stimuli. The Ba(2+)-evoked release was inhibited by 85% by 3 microM tetrodotoxin and 95% by 5 microM nifedipine. Ba2+ also increased the potency of K(+)-evoked release of [3H]noradrenalin, as maximal release was observed with 60 mM K+ compared with the 100 mM K+ necessary to achieve maximal release in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…For this reason, in this experiment, Ba 2+ was utilized to decrease the K + permeability of the cell membrane, resulting in depolarization of the resting potential. Ba 2+ -induced depolarization in SH-SY5Y and Jurkat cells has been reported in previous studies 27,28 .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…For this reason, in this experiment, Ba 2+ was utilized to decrease the K + permeability of the cell membrane, resulting in depolarization of the resting potential. Ba 2+ -induced depolarization in SH-SY5Y and Jurkat cells has been reported in previous studies 27,28 .…”
Section: Resultssupporting
confidence: 81%
“…Ba 2+ was chosen because it inhibits several types of two-pore-domain potassium channels 37,38 , which predominantly regulate the resting membrane potential. Previous studies have confirmed that Ba 2+ depolarizes the membrane potential in SH-SY5Y and Jurkat cells 39,40 .…”
Section: In Vitro Changes In Mr Parameters Induced By Membrane Potentialmentioning
confidence: 68%
“…To examine this possibility, we investigated the ability of muscarine to inhibit PH]-NA release evoked by other stimuli. We have previously shown that Ba2+ evokes release in these cells via depolarization and Ca2" influx through voltage-gated Ca2" channels (Vaughan et al, 1993b). Figure 3 shows that release evoked by substitution of extracellular Ca2" with Ba2+ (2.5 mM) for 4 min, and also by 4 min exposure to 28 JIM veratridine (another commonly used depolarizing secretagogue) can be inhibited to similar degrees as K+-evoked release with 300 jAM muscarine.…”
Section: Muscarinic Inhibition Of [3h]-na Release Occurs Via Pertussimentioning
confidence: 85%